A Facile Synthesis of Mesoporous TiO2 Sub-Microsphere Host for Long Life Lithium-Sulfur Battery Cathodes. (10th June 2017) - Sun, Yan; Zhao, Yining; Cui, Yingxue; Zhang, Jing; Zhang, Guofeng; Luo, Wenhao; Zheng, Wenjun
Graphical abstract: An ionic liquid assisted hydrothermal synthesis of mesoporous TiO2 host for lithium-sulfur battery cathode is proposed, the unique highly porous structure of our product can realize a capacity retention of 78.1% and a decay rate of 0.07% per cycle over 300 cycles at a current rate of 0.1C. Highlights: Highly porous TiO2 sub-microspheres have been synthesized by hydrothermal method. The ionic liquid used in the reaction plays a crucial role in morphology control. The MS TiO2 product owns excellent adsorption ability toward polysulfides. MS TiO2 -S cathode exhibits good cycling stability and low capacity decay rate. Abstract: Mesoporous titanium dioxide sub-microspheres (MS TiO2 ) have been prepared by a facile one-step hydrothermal synthesis method with the existence of 1-carboxyethyl-3-methylimidazolium chloride ionic liquid ([HOOCEMIM][Cl](IL) ). The [HOOCEMIM][Cl](IL) used in the experiment played a crucial role in triggering self-assembly of primary TiO2 nanoparticles. The obtained MS TiO2 material has an excellent porous structure with a large pore volume of 0.792 cm 3 g −1 and a large specific surface area of 291.08 m 2 g −1 . This unique structure can realize effective contact between host material and lithium polysulfide intermediates, thus promote the adsorption performance chemically. In addition, the 3D mesoporous structure can physically confine the intermediate products to the electrode and also accommodate the volume expansion of sulfur upon cycling. The MS TiO2 and sulfur (MS TiO2 -S) composite cathode exhibited superior rate capacity and long term cycling stability than that of the commercial TiO2 and sulfur (C TiO2 -S) composite cathode, displaying a very low capacity decay rate of 0.07% per cycle over 300 cycles. Even when the sulfur content of the MS TiO2 -S composite is up to 84 wt.%, the capacity decay rate still remains at a relatively low level.